Enhancing Writing Skills through Digital Collaborative Platforms in Language Learning (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Digital collaborative platforms have revolutionized the way language learners engage in writing activities by facilitating real-time collaboration, feedback exchange, and interactive learning environments. This article explores the use of digital collaborative platforms to enhance writing skills in language learners. By enabling students to co-create texts, provide peer feedback, and access diverse writing resources, these platforms foster collaborative learning and improve writing proficiency. The article discusses theoretical foundations, benefits, practical strategies, and case studies demonstrating the effectiveness of digital collaborative platforms in supporting language development.